Towards a Digital Poetics - O'Sullivan, James. author. aut Link
XVIII, 146 p. 5 illus., 2 illus. in color.
Keywords: We live in an age where language and screens continue to collide for creative purposes, giving rise to new forms of digital literatures and literary video games. Towards a Digital Poetics explores this relationship between word and computer, querying what it is that makes contemporary fictions like Dear Esther and All the Delicate Duplicates—both ludic and literary—different from their print-based predecessors.